The Effect of Using QRIS Payment System on Increasing Sales Turnover (Case Study of MSMEs in Deli Serdang Regency) - Rebecca Luxciana Siahaan; Indra Siregar; Martolop Sinambela (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
This study aims to determine the effect of using the QRIS payment system on increasing MSME sales turnover. The type of research used in this study is quantitative. The population used in this study is MSMEs located in Deli Serdang Regency. The number of respondents consisted of 95 MSMEs with probability sampling and sampling techniques using accidental sampling. The results showed that the use of the QRIS payment system had a positive and significant effect on increasing MSME sales turnover partially. The results of the R Square value showed that the variable of using the QRIS payment system affected the increase in sales turnover by 5.8%, while the remaining 94.2% was influenced by other variables outside the research of this author.